Human capital diversity and entrepreneurship: Results from the regional individual skill dispersion nexus on self-employment activity - Dirk Oberschachtsiek (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
Human capital has been shown to be highly important in the venture creation process. In this study, we account for the fact that human capital on the individual and regional levels may be interrelated in affecting entrepreneurship. We use German survey data, which allow us to focus on a specific measure of human capital (diversity in task experience) and to study the individual and regional levels. Our research provides evidence for the thesis that diverse human capital increases the level of entrepreneurship activity via individual and aggregated pathways and that the price elasticity of diverse human capital in affecting business activity is low.
Keywords: L26; J23; J24; 330; entrepreneurship capital; human capital; nascent entrepreneur; multilevel analysis